Secure and Efficient Classification of Trusted and Untrusted Nodes in Wireless Body Area Networks: A Survey of Techniques and Applications - Al Barazanchi I.I.; Hashim W.; Thabit R.; Sekhar R.; Shah P.; Penubadi H.R. (Springer Science and Business Media Deutschland GmbH, 2025)
This review examines Wireless Body Area Networks (WBANs) and their safe and efficient trusted and untrusted node categorization. WBAN data transmission must be secure due to the extensive use of wearable devices and the growing importance of health monitoring. This study reviews methods and applications used to verify network nodes? trustworthiness. Through a detailed analysis, we examine WBAN security and efficiency issues, evaluate existing methods, and highlight their strengths and weaknesses. This paper addresses the crucial issue of categorizing nodes as trusted or untrusted in Wireless Body Area Networks. Secure data transfer in WBANs is crucial as wearable gadgets and health monitoring grow more popular. This research aims to thoroughly investigate WBAN node classification methods and applications for safe and efficient classification. This comprehensive research helps identify security and efficiency issues in these networks and evaluate existing methods. This study can benefit academics, practitioners, and stakeholders interested in WBAN development and implementation. The research illuminates the current advances in safe and efficient node classification, enabling experts to improve WBAN security architecture. This study helps build dependable wireless networks for health monitoring and other uses, advancing wearable technology. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.